Chronic effects of a dynamic stretching and core stability exercise protocol on physical performance in u-16 volleyball players - Mancini, A.; Cosco, L. F.; Monda, V.; Emerenziani, G. P.; Martone, D.; Buono, P. (Sports, 2025)
Background: Volleyball requires explosive jumps, agility, and upper and lower limb coordination. Dynamic stretching (DS) and core stability (CS) protocols are often used separately in training sessions, but little is known about their combined effects on the performance in adolescent players. This study aimed to investigate the impact of a 12-week integrated DS and CS program (StretCor), in addition to standard training, on physical performance in U-16 volleyball players.